THE INFLUENCE OF CEO EX-AUDITOR BACKGROUND, CEO EXPERT POWER, AND CEO OWNERSHIP POWER ON FINANCIAL STATEMENT READABILITY - Renna Magdalena; Oliandes Sondakh; Chavella Janice Davalin Wijaya (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
This study examines the influence of three CEO characteristics—prior experience as an auditor (Ex-Auditor), expert power, and ownership power—on the readability of financial statements in the banking sector in Indonesia. The sample includes 42 banks listed on the Indonesia Stock Exchange (IDX), observed over four years from 2020 to 2023, resulting in 168 firm-year observations. Purposive sampling was used to select firms that disclosed relevant CEO information and published financial statements in English. Readability was assessed using the Gunning Fog Index, which was explicitly applied to the narrative disclosures in the notes and financial statements. Results from multiple linear regression analysis show that CEO Ex-Auditor experience and CEO Expert Power significantly and positively affect financial statement readability. In contrast, CEO Ownership Power does not exhibit a vital influence. These findings underscore the role of experience-based leadership in enhancing the clarity and transparency of corporate financial disclosures.